The economic impact of demographic structure in OECD countries - Yunus Aksoy; Tobias Grasl; Ron P. Smith (Center for Economic Studies and ifo Institute (CESifo), 2012)
We examine the impact of demographic structure, the proportion of the population in each age group, on growth, savings, investment, hours, interest rates and inflation using a panel VAR estimated from data for 20 OECD economies, mainly for the period 1970-2007. This flexible dynamic structure with interactions among the main macroeconomic variables allows us to estimate long-run effects of demographic structure on the individual countries. Our estimates confirm the importance of these effects.
Keywords: E32; J11; 330; demographic changes; macroeconomic variables; business cycle; Bevölkerungsstruktur; Bevölkerungsökonomie; Makroökonomischer Einfluss; Konjunktur; OECD-Staaten